2009
DOI: 10.3748/wjg.15.1264
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoid hyperemesis syndrome: Clinical diagnosis of an underrecognised manifestation of chronic cannabis abuse

Abstract: Cannabis is a common drug of abuse that is associated with various long-term and short-term adverse effects. The nature of its association with vomiting after chronic abuse is obscure and is underrecognised by clinicians. In some patients this vomiting can take on a pattern similar to cyclic vomiting syndrome with a peculiar compulsive hot bathing pattern, which relieves intense feelings of nausea and accompanying symptoms. In this case report, we describe a twentytwo year-old-male with a history of chronic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
91
1
8

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 14 publications
5
91
1
8
Order By: Relevance
“…With more recent research, these symptoms of recurrent nausea, vomiting, and abdominal pain have been identified as a medical condition named cannabinoid hyperemesis syndrome (CHS). The triad of symptoms of CHS is identified in recent studies as nausea, vomiting, and abdominal pain, relieved by taking hot baths or showers (Simonetto, Oxentenko, Herman, & Szostek, 2012;Sontineni, Chaudhary, Sontineni, & Lanspa, 2009;Soriano-Co, Batke, & Cappell, 2010;Sun & Zimmerman, 2013). These studies supported the findings of Allen et al's (2004) study.…”
supporting
confidence: 82%
“…With more recent research, these symptoms of recurrent nausea, vomiting, and abdominal pain have been identified as a medical condition named cannabinoid hyperemesis syndrome (CHS). The triad of symptoms of CHS is identified in recent studies as nausea, vomiting, and abdominal pain, relieved by taking hot baths or showers (Simonetto, Oxentenko, Herman, & Szostek, 2012;Sontineni, Chaudhary, Sontineni, & Lanspa, 2009;Soriano-Co, Batke, & Cappell, 2010;Sun & Zimmerman, 2013). These studies supported the findings of Allen et al's (2004) study.…”
supporting
confidence: 82%
“…Seven unique diagnostic frameworks were identified [6,9,30,51,[119][120][121]. There was a significant overlap among major diagnostic characteristics between the authors.…”
Section: Diagnosis Of Chsmentioning
confidence: 99%
“…Since 2004, 13 case reports and 3 small case series, the largest of which consisted of 9 patients, have been published in further support of CH. [4][5][6][7][8][9][10] In 2009, Sontineni et al 7 described important clinical features of CH, which included long-term cannabis use, cyclic vomiting, colicky abdominal pain, compulsive use of hot showers, and improvement of symptoms with cannabis cessation.…”
mentioning
confidence: 99%